Determination of The Rotational Friction Coefficients of Solid Cylinder with Various Inclined Plane Angle - Firdaus, T.; Toifur, M.; Pramudya, Y. (Department of Physics, Faculty of Mathematics and Natural Sciences, 2019)
The layer texture differences of an object have an influence on the friction force caused by both planes. This research aims to determine the static and kinetic friction coefficient on several solid cylinder materials. The benefits of this research can be used to develop experimental learning activities on friction coefficient. This research used experimental method. The research was carried out by rolling samples at various inclined plane angles and measuring the traveled distance traveled in one rotation (D). The results showed that the static and kinetic friction coefficients between aluminum cylinder and glass were 0.146 and 0.097, iron cylinder and glass were 0.136 and 0.096, glass cylinder and brass were 0.132 and 0.094, nylon cylinder and glass were 0.101 and 0.090, and stainsless cylinder and glass were 0.122 and 0.094, respectively.Perbedaan tekstur lapisan sebuah benda mempunyai pengaruh pada gaya gesek yang ditimbulkan oleh kedua bidang. Penelitian ini bertujuan untuk menentukan nilai koefisien gesek statis dan koefisien gesek kinetik pada beberapa bahan silinder pejal. Manfaat yang dapat diambil dari hasil penelitian ini adalah dapat digunakan sebagai mengembangkan kegiatan pembelajaran praktikum koefisien gesekan benda. Penelitian ini menggunakan metode eksperimen. Penelitian dilaksanakan dengan menggelindingkan sampel pada berbagai sudut kemiringan dan mengukur jarak tempuh untuk satu kali putaran (D). Hasil penelitian menunjukkan bahwa nilai koefisien gesek statis dan koefisien gesek kinetik secara berurutan untuk silinder aluminium dengan kaca sebesar 0,146 Ã‚Â dan 0,097,Ã‚Â untuk silinder besi dengan kaca sebesar 0,136 dan 0,096, untuk silinder kuningan dengan kaca 0,132 dan 0,094, untuk silinder nylon dengan kaca sebesar 0,101 dan 0,090, dan untuk stainsless dengan kaca sebesar 0,122 dan 0,094.